Wiedergeboren in Westfalen - Liebheit, Melanie (Germany : Luethje ; Schneider Filmproduktion ; HFF Munich, 2008)
In the middle of the German province priest Sri Paskaran built the biggest Tamil Hindu temple in Europe. In 2002, he inaugurated the temple amidst industrial plants in the Westphalian village of Hamm-Uentrop. Since then, colorful and sonorous ceremonies honor the goddess in the land of the down-to-earth Westphalians. The film accompanies the priest in his busy daily routine and during his arrangements for the annual temple festival, which 20,000 believers are expected to attend. In the neighborhood, the locals cultivate their own traditions during the fair, which includes shooting matches. Irene sells fast-food sausages in the local snack-bar, and farmer Externbrink has got a sacred cow in his barn. An encounter and coexistence of two universes full of contrast.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films